Analisis Filosofis Konsep Profil Pelajar Pancasila dalam Kurikulum Merdeka: Tinjauan Teori Pendidikan Karakter - zain, Muhammad afnan (Maliki Interdisciplinary Journal, 2026)
This study presents a philosophical and conceptual analysis of the Pancasila Student Profile (PPP) as the main foundation for implementing the Merdeka Curriculum. The PPP is formulated as a holistic effort to shape students into citizens who are characterized, creative, and competent, in line with the nation's noble values. The research approach is a qualitative literature study focusing on conceptual interpretation, comparison of global character education models, and tracing the philosophical roots of Pancasila values within the educational framework. The objective of this research is to identify the essential dimensions of the PPP and analyze their compatibility with prominent character education theories, linking them to the Islamic education perspective, which is widely studied at institutions such as UIN Malang (Sahlan, 2020). The analysis results indicate that the PPP, with its six dimensions (Faithful, Independent, Gotong Royong, Globally Diverse, Critically Reasoning, and Creative), offers a unique synthesis between universal ethics and national identity. The main conclusion affirms that the implementation of the Merdeka Curriculum demands a fundamental paradigm shift among teachers and the educational ecosystem to consistently realize these values through context-based and school-culture projects, reflecting the need for transformation in madrasahs and educational institutions (Wahyuni, 2021).